THE EFFICACY OF PULSED ELECTROMAGNETIC FIELD ON CERVICAL DISC HERNIATION - Hayder Hashim Ahmed (Scholars Digest Publishing, 2025)
In recent years, neck pain has become a widespread phenomenon in society. It attributes many reasons, such as little movement and non-practice sports, to weak muscles. Besides, noon or the nature of some professions, like business, handmade and sitting in offices and on computers and leadership, for a long time. Finally, the psychological anxiety causes some neck-shrivel cervical vertebrae. Ignorance, then, of such dangerous injury results in some shrivelled fragments. The study evaluated the effectiveness of pulsed electromagnetic field (PEMF) therapy in improving functional and structural symptoms in patients with cervical disc herniation. A randomized sample of 60 patients was divided into two groups: an experimental group receiving PEMF therapy alongside a conventional treatment protocol and a control group receiving traditional treatment alone. Results showed a significant improvement in pain intensity, neck functional index, and MRI parameters in the PEMF therapy group compared to the control group. The study concluded that PEMF therapy could be an effective and safe complementary intervention for cervical disc herniation and recommended further long-term studies to evaluate its lasting effects.